국내 유통 김치 중 N-Nitrosodimethylamine과 그 전구물질의 함량 분석 및 안전성 평가 - 강경훈(Kyung Hun Kang); 김성현(Sung Hyun Kim); 김상현(Sang-Hyun Kim); 김정균(Jeong Gyun Kim); 성낙주(Nak-Ju Sung); 임희경(Heekyung Lim); 정미자(Mi Ja Chung) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2017)
Dimethylamine (DMA), nitrate, nitrite, and biogenic amines (BA) are precursors of carcinogenic N-nitrosamines. This study investigated contamination levels of DMA, nitrate, nitrite, and BA in various types of Korean commercial kimchi such as Baechu kimchi, Kkakduki, Chonggak kimchi, Matkimchi, ripened Baechu kimchi, and Baek kimchi. The average DMA, nitrate, and nitrite levels in Baechu kimchi were 29.7, 2,178.8, and 3.0 mg/kg, respectively. Low levels of DMA and nitrate were detected in Kkakduki. Tryptamine, putrescine, cadaverine, tyramine, and spermidine were detected in kimchi with exclusion of Baek kimchi and Chonggak kimchi. Tryptamine in Baek kimchi was only present in trace amount, and spermidine was not detected in Chonggak kimchi. The average tryptamine, putrescine, cadaverine, tyramine, and spermidine levels in Baechu kimchi were 15.0, 64.6, 18.0, 44.0, and 7.8 mg/kg, respectively. A low level of tyramine was detected in Kkakduki. In addition, contamination of N-nitrosodimethylamine (NDMA) was detected in Kkakduki at a level of $1.38μg/kg$. Daily exposure to NDMA in the consumer only group was estimated using average daily Kkakduki consumption and average body weight of the total population. The estimated daily intake of NDMA by Kkakduki was $2.31{×}10^{-7}mg/kg\;b.w./d.$ The margin of exposure to NDMA for the general population was 259,924. Accordingly, the health risk from NDMA caused by intake of Kkakduki was considered to be very low. Dimethylamine(DMA), 질산염, 아질산염, biogenic amines은 발암성 니트로사민의 전구물질이다. 본 연구는 국내 상품 김치로 유통되고 있는 국내산 배추김치, 깍두기, 총각김치, 맛김치, 묵은김치, 백김치의 김치 내 DMA, 질산염, 아질산염, biogenic amines의 오염도를 조사하였다. 배추김치 내 DMA, 질산염, 아질산염 함량은 각각 29.7, 2,178.8, 3.0 mg/kg이었다. 김치 종류 중에서 깍두기의 DMA와 질산염 함량이 가장 낮았다. Tryptamine, putrescine, cadaverine, tyramine, spermidine이 백김치와 총각김치를 제외한 분석된 김치 내 검출되었다. 백김치 내 tryptamine이 단지흔적량 존재하고 spermidine은 총각김치에서는 검출되지 않았다. 배추김치 내 tryptamine, putrescine, cadaverine, tyramine, spermidine의 함량은 각각 15.0, 64.6, 18.0, 44.0, 7.8 mg/kg이었다. 깍두기 내 tyramine의 함량이 낮았다. 깍두기 내 NDMA의 오염도를 분석하였고, 그 평균 함량은 $1.38μg/kg$이었다. 깍두기 1일 평균 섭취량과 체중을 근거로 깍두기 섭취군의 NDMA 인체노출량을 산출한 결과 깍두기 섭취로 인한 NDMA 노출량은 $2.31{×}10^{-7}mg/kg\;b.w./d$로 나타났으며, 노출안전역(MOE)은 259,924로 위해 정도가 매우 낮은 안전한 수준으로 나타났다.